Analysis of Mathematical Literacy Ability of Students in terms of Visual Learning Styles and Gender Differences - Dian Ulfa Sari; Deti Sri Rahayu (Universitas Sembilanbelas November Kolaka, 2021)
The aim of this study was to determine the mathematical literacy skills of grade VIII students (male and female) based on visual learning styles at SMP Negeri (State Middle School) 2 Kendari. This study used an exploratory method with a qualitative approach. Results of the study indicated that: (1) as seen from solving problems related to quantity content aspect, female students with a visual learning style had not been able to pass the stage of using mathematical tools; on space and shape content aspect they were able to pass all stages; meanwhile on change and relationships content aspect the female students were also able to pass all stages. (2) seen from quantity content aspect to solve problem, male students with a visual learning style had not been able to pass the stages of formulating and planning strategies as well as using mathematical tools; on space and shape content aspect they were able to pass all stages; and on change and relationship content aspect, the male students were able to pass all stages.Female students with visual learning styles have not been able to go through one stage, namely the stage of using mathematical tools. While male students with a visual learning style have not gone through two stages, namely te stage of formulating and planning strategies then the stage of using mathematical tools.